2004
DOI: 10.7863/jum.2004.23.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Perianal Inflammatory Disease

Abstract: Combined gray scale and color Doppler sonography enables a high detectability rate and comprehensive characterization of perianal abscesses and fistulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…It allows clarification of the vascular anatomy and architecture as well as better differentiation of neoplastic and inflammatory processes. Cross-sectional images provide better panoramic views and allow better 3D reconstruction than single ultrasound images 94 .…”
Section: Perineal Ultrasoundmentioning
confidence: 99%
“…It allows clarification of the vascular anatomy and architecture as well as better differentiation of neoplastic and inflammatory processes. Cross-sectional images provide better panoramic views and allow better 3D reconstruction than single ultrasound images 94 .…”
Section: Perineal Ultrasoundmentioning
confidence: 99%
“…Recent studies have reported that TPUS is accurate for detecting perianal fistulas and perianal abscesses [6,7,8,15]. In the published medical literature, the sensitivity, specificity, and positive predictive value of TPUS for detecting fistulas has been reported to be 84.9%-100%, 80%-100%, and 86.5%, respectively [6-8,16].…”
Section: Discussionmentioning
confidence: 99%
“…In the published medical literature, the sensitivity, specificity, and positive predictive value of TPUS for detecting fistulas has been reported to be 84.9%-100%, 80%-100%, and 86.5%, respectively [6-8,16]. The detectability of TPUS increased slightly in combination with a color Doppler study [7]. …”
Section: Discussionmentioning
confidence: 99%
“…The Parks classification is reported in Figure 4 . Among the available data, Mallouhi et al firstly reported a sensitivity of 100% and a specificity of 94–100% of TPUS in detecting perianal fistulas and abscesses in a cohort of 62 IBD patients [ 44 ].…”
Section: Crohn’s Disease In Bowel Ultrasoundmentioning
confidence: 99%